Study on the Self-Discharge of an All-Vanadium Redox Flow Battery through Monitoring Individual Cell Voltages - Chou Y.-S.; Devi N.; Yen S.-C.; Singh P.; Chen Y.-S. (My University, 2025)
Power generation from renewable energy sources along with energy storage systems for consistent power supplies might be a solution to attain net-zero carbon emissions. Recently, all-vanadium redox flow batteries (VRFBs) have gained popularity because of their long cycle life, ease of maintenance, and flexible power/capacity configurations. Understanding the process of cell response over time is deemed to be essential for settling the performance-limiting factors. The main phenomenon linked with the battery stack that causes battery deterioration is self-discharge. Here, this study involves the performance testing of a 19-cell VRFB for both lab- and pilot-scale electrolyte designs. Graphite bipolar plate sides were designed with additional extensions and three voltage measuring holes. Each electrolyte volume and flow rates were 4.0 and 250 L and 2.0 and 4.0 L min-1 for lab-scale and pilot-scale studies, respectively. Battery efficiencies are examined at various current density levels from 10 to 60 mA cm-2. Individual cell voltages are monitored to study the self-discharge of a VRFB. The study of battery stability and voltage distribution for individual cells leads to the conclusion that the potential difference at centrally located cells contributes significantly to battery self-discharge. This study is significant for an understanding of the limiting factors for developing VRFB-based grid energy storage. © 2022 American Chemical Society.